2021
DOI: 10.1089/tmj.2020.0256
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction with Use of Telemedicine in University Clinic of Psychiatry: Skopje, North Macedonia During COVID-19 Pandemic

Abstract: Background: There is increasing interest in the use of telemedicine as a means of health care delivery especially in circumstances of pandemics. This is partly because technological advances have made the equipment less expensive and simpler to use and partly because increasing health care costs and patient expectations have increased the need to find alternative modes of health care delivery. Introduction: Telemedicine and telepsychiatry, in particular, are rapidly becoming important delivery approaches to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 6 publications
3
52
1
Order By: Relevance
“…26 For rehabilitation, 80% of the virtual visits were for follow-ups for established issues. 27 The main benefits of telemedicine reported by patients were time saved due to lesser traveling 3,7,20,22,23,[27][28][29][30][31][32][33] and waiting in queues, 20,23,29,31,34 cost efficiency, 3,27,29,30,32,33,35 convenience, 7,26,27,31,33,[36][37][38] , and accessibility. 7,25,32,[35][36]39 Telemedicine was found satisfactory on various outcome measures such as addressing patients' concerns and questions, 38 communication with health care providers, 3,32 development of a treatment plan, 25,27 comprehensibility of disease, 31 usefulness, 23,24,…”
Section: Professionals New York-presbyterian/weill Cornell Medicalmentioning
confidence: 99%
“…26 For rehabilitation, 80% of the virtual visits were for follow-ups for established issues. 27 The main benefits of telemedicine reported by patients were time saved due to lesser traveling 3,7,20,22,23,[27][28][29][30][31][32][33] and waiting in queues, 20,23,29,31,34 cost efficiency, 3,27,29,30,32,33,35 convenience, 7,26,27,31,33,[36][37][38] , and accessibility. 7,25,32,[35][36]39 Telemedicine was found satisfactory on various outcome measures such as addressing patients' concerns and questions, 38 communication with health care providers, 3,32 development of a treatment plan, 25,27 comprehensibility of disease, 31 usefulness, 23,24,…”
Section: Professionals New York-presbyterian/weill Cornell Medicalmentioning
confidence: 99%
“…In the context of the COVID-19 global pandemic, remote telecommunication methods have become much more common place in mental health settings. A study conducted at a University Clinic reported using the short form patient satisfaction questionnaire (PSQ-18) [22] that overall satisfaction with psychiatric care was high [23] whilst another observed that the frequency of patient contact within a community psychiatry service was maintained using remote telecommunication consultations and that prescribing practices were largely unaffected [24]. For adults, the COVID-19 related literature in Autism is not developed, although there is some discussion in the literature pertaining to children [25].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in an effort to fast track COVID-19 tests, the US Food and Drug Administration has waived the standard regulations to accelerate and permit test makers to commercialize scientifically valid products in the US [34]. Also, medical care systems in Houston, Texas developed a remote communication channel between emergency responders and physicians to help with triaging [6,9]. Virtual home treatment for high risk individuals and remote/ digital Intensive Care Unit (ICU) monitoring is also being used to decrease hospital staff contact with patients with confirmed or suspected cases of COVID-19 [8,42].…”
Section: Recent Policies and Trends For Telemedicine Integration During Covid-19 Pandemicmentioning
confidence: 99%
“…Evidence from the literature [6][7][8] suggests that there is increasing interest in the adoption of telemedicine to provide health care especially due to the pandemic. Telemedicine, which was introduced in the early twentieth century, involves the use of telecommunication and online technologies, including mobile devices and computers for delivery of health care or services [9].…”
Section: Introductionmentioning
confidence: 99%